Uji Potensi Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) Terhadap Peningkatan Ketebalan Jaringan Granulasi dan Waktu Penyembuhan Luka Bakar Tikus - Betriksia, Dea; Hamid, Iwan Syahrial; Hermanu, Liliek Suyatmiatun (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Burns are skin damage caused by high-temperature which contact to the skin. Second-degree burns are the most common accident at home. The process of wound healing can be accelerated using traditional medicines, one of which is Binahong (Anredera cordifolia (Ten.) Steenis). Binahong contains saponins, flavonoids, alkaloids, tannins, and steroids which have been shown to accelerate the wound healing process in previous experiments. The purpose of this study was to analyze the potential of binahong leaf extract to increase granulation tissue thickness and reduce healing time of burns. This study uses an experimental method. Wistar rats were used in this study, which were divided into 4 groups, namely K (-), K (+), and treatment groups namely the concentration of binahong leaf extract 20% (P1) and 40% (P2). Burns are made using an iron plate that has been heated to 95° C and pasted for 30 seconds on the lower back of the mouse to cause second-degree burns. The binahong leaf extract used in this study was made in the form of an ointment and given twice a day for 7 days. Increased granulation tissue thickness and wound healing time were observed on day 3 and day 7. The results showed an increase in granulation tissue thickness and shorter healing time in the experimental group given binahong leaf extract with a concentration of 40% (P2) compared to the experimental group that was given binahong leaf extract with a concentration of 20% (P1).